THE RELATIONSHIP BETWEEN VITAMIN D DEFICIENCY DUE TO INDOOR ACTIVITY AGAINST OSTEOPOROSIS: SCOPING REVIEW - Nopitarose, Lia; Saryono, Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction: Lack of sun exposure due to lack of outdoor activities can lead to vitamin D deficiency. Vitamin D is an important regulator of calcium metabolism so its presence is very important for life and vitamin D deficiency is common throughout the world. Based on data from the International Osteoporosis Foundation (IOF), more than 200 million women in the world suffer from osteoporosis, with the majority of women aged over 60 years. The purpose of this scoping review was to determine the relationship between vitamin D deficiency due to indoor activity and the occurrence of osteoporosis. This research was conducted using the scoping review method, which was a database search for several articles from international journals related to vitamin D deficiency, indoor activity and osteoporosis. The databases used in this study were Pubmed, Science Direct and Google Scholar there were 664 articles obtained. After screening the articles with inclusion and exclusion criteria, 16 articles were deemed relevant. Then, the researchers reviewed and analysed the articles for the review article. The conclusion from this scoping review is that vitamin D deficiency can be caused by a lack of sun exposure due to indoor activities which are a lifestyle and daily activities at work. Meanwhile, vitamin D deficiency can lead to an increased risk of osteoporosis through less than optimal bone and muscle function and increased bone turnover as a result of increased levels of parathyroid hormone (PTH).